Performance Analysis of Service System in Health Care Network - Wagle, Bharat Raj; Ghimire, Ram Prasad (Nepal Journal of Mathematical Sciences, 2021)
This study is based on a case study research design. The approach for the study is adapted from Monte-Carlo simulation models. The study model can fit a finite number of patients who can join in the queue in different counters and performance of the selected counter in a particular time. The data are collected through direct observation with the help of a checklist. Out of 150 patients, 50 patients are observed in each new, old, and reserved (ex-army Indian pensioner and health insurance policy holder) counter. Our main findings are mean number of patients waiting in queue, mean number of patients in the system, mean time of patient waiting in queue, the time spent by a patient in the system, Average time that the server is idle, the percentage of the time that the server is busy. The study concludes that the service provided in the old counter is satisfactory to some extent. The research has been come up with the model design to estimate patients demand in the counters and it uses mean arrival time and mean service time.